Handgrip strength and the GLIM criteria are markers for nutritional risk in patients treated in the SUS (Government Health System) - Leandro-Merhi, Vânia Aparecida; Mazzini, Lucas Rosasco; Stopiglia, Larissa Silveira; Teixeira, Julia Pizzo; Barbieri, Vitor Alexandre Camargo; Seccacci, Rafael Iglesias (Frontiers in Nutrition, 2025)
BackgroundAlthough several tools are available for nutritional diagnosis, some difficulties may be encountered in the assessment of bedridden patients.ObjectiveTo investigate the validity and feasibility of the Global Leadership Initiative on Malnutrition (GLIM) criteria and the handgrip strength (HGS) as markers of nutritional status in comparison with the Nutritional Risk Screening-2002 (NRS) and the Subjective Global Assessment (SGA) in patients hospitalized under the Government Health System.MethodCross-sectional study conducted with patients in the surgical wards of a university hospital. Clinical and nutritional data were investigated using the GLIM criteria, HGS, NRS and SGA. The Chi-square or Fisher’s exact test, Mann–Whitney test, Kappa coefficient and simple and multiple logistic regression analysis were used for data analysis, with stepwise variable selection criteria and a significance level of 5%. The statistical software used for the analyses was the Statistical Analysis System (SAS).ResultsA total of 160 patients were assessed; their mean age was 59.31 ± 16.14 years. Out of these, 62.5% (n = 100) were male and 37.5% (n = 60) female. By multiple regression analysis it was found that HGS (p = 0.0327; OR = 0.956 (1.046); IC95% = 0.917; 0.996 (1.004; 1.091) and the GLIM criteria (p = <0.0001; OR = 26.381; IC95% = 9.996; 69.620) were factors associated with nutritional risk according to the NRS. And only the GLIM criteria were the factor associated with malnutrition according to the SGA (p = <0.0001; OR = 27.710; IC95% = 11.306; 67.916). Malnutrition according to the GLIM criteria presented 26.4 times more chance of nutritional risk according to the NRS and 27.71 times more chance of malnutrition according to the SGA.ConclusionIn patients treated under the SUS (Government Health System), the HGS and the GLIM criteria were markers for nutritional risk according to the NRS. It is suggested that those tools could be incorporated into the routine nutritional care in the hospital setting by the Government Health System.